Revisiting the Impact of Trade Liberalization and Mergers on the Malting Industry of North America - Derek Brewin; Richard Gray; Giannis Karagiannis (German Journal of Agricultural Economics (GJAE), 2012)
This paper builds on the work of BUSCHENA and GRAY (1999) to look at the effects of mergers in the North American malting industry as ten firms in two separated markets merged into four firms in an integrated market. We explore the sensitivity of our results to the assumption of market power. We show that welfare gains from free trade are not generally lost but can face considerable redistribution under reasonable assumptions of market power. Varying the rival reactions did not change the result that total economic surplus with four firms after NAFTA is greater than when there were ten firms but no trade. Mergers reduce the trade gains of malt consumers and barley producers in both countries and reduce the welfare losses of malting plants in the U.S. According to our estimates, the second wave of mergers may have led to a positive total welfare effect for malting plants in Canada if the oligopoly is exercising significant market power.
Keywords: 330; Brauerei; Fusion; Marktintegration; Marktmacht; Wohlfahrtsanalyse; USA